HAWC observations of the acceleration of very-high-energy cosmic rays in the Cygnus Cocoon - Abeysekara, A. U.; Albert, A.; Alfaro, R.; Alvarez, C.; Camacho, J. R.Angeles; Arteaga-Velázquez, J. C.; Arunbabu, K. P.; Rojas, D. Avila; Solares, H. A.Ayala; Baghmanyan, V.; Belmont-Moreno, E.; BenZvi, S. Y.; et al. (Nature Astronomy, 2021)
Cosmic rays with energies up to a few PeV are known to be accelerated within the Milky Way1,2. Traditionally, it has been presumed that supernova remnants were the main source of these very-high-energy cosmic rays3,4, but theoretically it is difficult to accelerate protons to PeV energies5,6 and observationally there simply is no evidence of the remnants being sources of hadrons with energies above a few tens of TeV7,8. One possible source of protons with those energies is the Galactic Centre region9. Here, we report observations of 1–100 TeV γ rays coming from the ‘Cygnus Cocoon’10, which is a superbubble that surrounds a region of massive star formation. These γ rays are likely produced by 10–1,000 TeV freshly accelerated cosmic rays that originate from the enclosed star-forming region Cyg OB2. Until now it was not known that such regions could accelerate particles to these energies. The measured flux likely originates from hadronic interactions. The spectral shape and the emission profile of the Cocoon changes from GeV to TeV energies, which reveals the transport of cosmic particles and historical activity in the superbubble.
CRIS-Team Scopus Importer:2021-04-02